DNA-mediated gene transfer in Friend leukemia cells by cotransfection of simian virus 40 DNA with herpes simplex virus thymidine kinase DNA. - Steinheider, G (1983)
Thymidine kinase-negative Friend leukemia cells were cotransfected with simian virus 40 (SV40) DNA and thymidine kinase gene DNA of herpes simplex virus type 1. The transfected thymidine kinase-positive cells were selected in HAT medium, and SV40 T-antigen expression was observed over many months in cells cultured under selective conditions, and after adaptation to normal growth medium under nonselective conditions. It was shown by Southern blot hybridization that SV40 DNA was integrated in multiple copies in the chromosomal DNA of several clones. All SV40 DNA-containing Friend leukemia cell clones analyzed were able to undergo induced erythroid differentiation. Induced cultures still expressed SV40 T-antigen to the same extent that untreated control cultures did.